If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + 1)(m + 1) = 0 Reorder the terms: (1 + m)(m + 1) = 0 Reorder the terms: (1 + m)(1 + m) = 0 Multiply (1 + m) * (1 + m) (1(1 + m) + m(1 + m)) = 0 ((1 * 1 + m * 1) + m(1 + m)) = 0 ((1 + 1m) + m(1 + m)) = 0 (1 + 1m + (1 * m + m * m)) = 0 (1 + 1m + (1m + m2)) = 0 Combine like terms: 1m + 1m = 2m (1 + 2m + m2) = 0 Solving 1 + 2m + m2 = 0 Solving for variable 'm'. Factor a trinomial. (1 + m)(1 + m) = 0Subproblem 1
Set the factor '(1 + m)' equal to zero and attempt to solve: Simplifying 1 + m = 0 Solving 1 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + m = 0 + -1 m = 0 + -1 Combine like terms: 0 + -1 = -1 m = -1 Simplifying m = -1Subproblem 2
Set the factor '(1 + m)' equal to zero and attempt to solve: Simplifying 1 + m = 0 Solving 1 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + m = 0 + -1 m = 0 + -1 Combine like terms: 0 + -1 = -1 m = -1 Simplifying m = -1Solution
m = {-1, -1}
| (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 | | F(x)=-3x-8f(2) | | 5+4/x | | 3/x+2/5 | | 5/x-2/x | | 3/5(30x) | | 12(4x-8)=4(12x+9) |